KORELASI FUNGSI HATI TERHADAP DERAJAT PENYAKIT DEMAM BERDARAH DENGUE ANAK - Ani Kartini; Mutmainnah Mutmainnah; Ibrahim Abdul Samad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
Dengue Haemorrhagic Fever (DHF) may result acute liver failure. Although these cases are rare but is more common in children, and early identification of these infections is important to reduce the morbidity as well as mortality. The aim of this study was to know the determinations and the correlation of liver functions with the grade of Dengue Haemorrhagic Fever in children. This study was conducted by cross sectional, using data from the medical records of DHF patients who had liver function tests (AST, ALT, PT, aPTT and albumin) in the Laboratory of Clinical Pathology Dr. Wahidin Sudirohusodo Hospital Makassar from the period of July 2008 to June 2010. AST, ALT and albumin were tested using Cobas Integra 400, PT and aPTT were tested using Humaclot VA, and the data were analyzed with Spearman correlation test. There were fifty-five samples: 26 (47.3%) were males and 29 (52.7%) were females. We found 15 (27.3%) grade I, 13 (23.6%) grade II, 16 (29.1%) grade III and 11 (20%) grade IV patients. In this study are found that AST and ALT increased and there is a tendency of extending aPTT value but there was no significant correlation with the grade of DHF. The mean of albumin was lower in grade IV, there was a significant correlation between albumin and the grade of DHF (r=–0.375, p<0.05). In conclusion, there was a significant correlation between albumin and the grade of DHF. It is suggested that the routine albumin examination in DHF patients should be carried on to know whether a prevention of complications is needed to reduce the possibility of mortality.